Analysis of The Implementation of The Salam Contract in The Marketplace: A Critical View of Buying Orders on Shopee - Fuad Hadziq, M; Taufiq, Muhammad; Khusnul Khotimah (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2024)
The facts of online transactions have many differences in dissimilarity when ordering and suitability of goods received. This discrepancy caused problems afterward with many complaints, and the effect was not willing of each other. This study aims to find out how online buying and selling transactions are carried out through Shopee from a system of salam contracts in the sharia context. This research method uses qualitative methods to examine the fact of salam contract of shopee. The data source is primary data from site shopee and informant of buyer and seller. Researchers also use secondary data sources originating from literature-related research from journal scopus and sinta also reputable journal related this topic. The study results show that buying and selling online at Shopee has the same concept as implementing the salam contract. Online buying and selling transactions have advantages and disadvantages for sellers and buyers. Online buying and selling transactions can be a transition from implementing the salam contract, provided that both parties understand the same in terms of responsibility and trust. By system and the fact, buying and selling transactions at Shopee are said to be by the salam contract. Little research examine the topic, particularly in market place regarding shopee contract.